From Daily Wages to Daily Woes: Investigating Financial Literacy and Spending Habits of Daily Wage Earners - Santhosh Kumar, K (Apex Journal of Business and Management, 2025)
Daily wage workers represent a significant segment of the informal workforce not only in India but globally; however, attention to their financial welfare requires substantial improvement. This research investigates the complex relationship between financial literacy, spending behavior, and savings behavior among daily wage earners in the Kottayam district of Kerala. Employing a quantitative research design, data were collected from 250 respondents using structured questionnaires administered through face-to-face interviews. Structural Equation Modeling (SEM) was utilized to analyze the interrelationships among these latent constructs and their collective influence on savings behavior. The results reveal that both financial literacy and spending behavior significantly affect the savings patterns of daily wage workers. The SEM model evidenced strong validity and excellent goodness-of-fit, confirming the robustness of the findings. These results provide valuable insights into the financial behaviors of a socioeconomically vulnerable population, highlighting key areas for targeted intervention. The findings hold important implications for developing tailored financial literacy programs and inclusive policies aimed at enhancing financial resilience, encouraging prudent savings, and ultimately improving the economic well-being of daily wage earners.